2018
DOI: 10.1177/1093526618809230
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Anastomosing Hemangioma: Case Report and Review of Renal Vascular Tumors in Children

Abstract: The case involves a 10-year-old child who underwent a left radical nephrectomy for what was believed to be a Wilms' tumor. Histopath examination indicated a benign vascular lesion, subsequently determined to be an anastomosing hemangioma of the kidney. A comparison with the previously cited pediatric patients with renal vascular tumors is provided, and the inconsistent diagnostic terminologies for these conditions are highlighted. The therapeutic implications of these predominantly benign renal tumors, in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…In terms of the tumor capsule, most reports have shown no presence of capsules in AH. Similar to only a few previous reports [ 17 – 19 ], our case had a complete capsule. Unfortunately, the studies that have reported tumor capsules did not show imaging findings.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of the tumor capsule, most reports have shown no presence of capsules in AH. Similar to only a few previous reports [ 17 – 19 ], our case had a complete capsule. Unfortunately, the studies that have reported tumor capsules did not show imaging findings.…”
Section: Discussionsupporting
confidence: 91%
“…Grossly, anastomosing haemangiomas are typically small ranging from 0.1 cm to 12 cm (mean, 2.2 cm)[ 5 , 10 , 17 ]. These tumours are often well-demarcated spongy mahogany brown masses[ 5 ].…”
Section: Anastomosing Haemangioma Of the Kidneymentioning
confidence: 99%